Secondary vocational education: Political context and school practices of a discontinued education offer - António Pinto; Fernando Rodrigues Silva; Paulo Delgado; Fernando Diogo (Arizona State University, 2020)
Vocational courses in secondary education within the Portuguese educational system, defined in Portaria no. 276/2013, of 23rd August, and based on the German Dual Training System, discontinued in 2016-2017. This exploratory study is the result of an analysis carried out with the actors involved in secondary education vocational courses of two schools in the area of Oporto. A mixed methodology was used applying a survey questionnaire to students and interviews with course and class directors, to verify to what extent these courses meet the goals set for their creation. Through this data analysis and interpretation, it is clear that students perceived the course as easy and motivating, due to its practical nature and its potential for access to the labour market. They also valued the competence and performance of the teachers who teach these courses. These directors also emphasized that the vocational school dropout numbers are related to the excessive theoretical content, a view that is supported by students. Nevertheless, it can be observed that the success rates are significant, fulfilling one of the main objectives that were outlined for these courses.